2022
DOI: 10.1007/s00259-022-05846-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of advanced semi-quantitative amyloid PET analysis methods

Abstract: Purpose To date, there is no consensus on how to semi-quantitatively assess brain amyloid PET. Some approaches use late acquisition alone (e.g., ELBA, based on radiomic features), others integrate the early scan (e.g., TDr, which targets the area of maximum perfusion) and structural imaging (e.g., WMR, that compares kinetic behaviour of white and grey matter, or SI based on the kinetic characteristics of the grey matter alone). In this study SUVr, ELBA, TDr, WMR, and SI were compared. The latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Global SUVR is a standard and valuable parameter for assessing the degree of global Aβ accumulation, increasingly used in antiamyloid clinical trials and for staging an individual’s Aβ pathology progression. In our study, global SUVR effectively distinguished the Aβ+ group from the Aβ– group with an impressive AUC of 0.963 at an SUVR threshold of 1.18. This cutoff value closely approximated the global SUVR thresholds reported in previous [ 18 F]Florbetapir PET/CT studies, despite minor differences in data collection methods and reference brain regions. Furthermore, we conducted an analysis of the correlations between plasma AD biomarkers and the global SUVR of [ 18 F] 92 to assess the consistency of cerebral Aβ deposition with plasma biomarkers.…”
Section: Resultsmentioning
confidence: 59%
“…Global SUVR is a standard and valuable parameter for assessing the degree of global Aβ accumulation, increasingly used in antiamyloid clinical trials and for staging an individual’s Aβ pathology progression. In our study, global SUVR effectively distinguished the Aβ+ group from the Aβ– group with an impressive AUC of 0.963 at an SUVR threshold of 1.18. This cutoff value closely approximated the global SUVR thresholds reported in previous [ 18 F]Florbetapir PET/CT studies, despite minor differences in data collection methods and reference brain regions. Furthermore, we conducted an analysis of the correlations between plasma AD biomarkers and the global SUVR of [ 18 F] 92 to assess the consistency of cerebral Aβ deposition with plasma biomarkers.…”
Section: Resultsmentioning
confidence: 59%
“…The scenario of presurgical fMRI mandates control for false negative results and alternative thresholding approaches have been suggested for this purpose [34]. As further clinical neuroimaging analogies, imaging data such as those obtained from computed tomography perfusion in acute ischemic stroke [35] or beta amyloid positron emission tomography [36] are usually viewed or analysed without fixed thresholding in order to avoid biases. In order to provide more information than typical main article figures, more detailed maps (e.g.…”
Section: Supplementary Reporting Of Unthresholded Results Mapsmentioning
confidence: 99%
“…A recent study reported good performance in predicting the endotype of CRSwNP using radiomics based on sinus CT data, with an AUC of 0.815 [ 13 ]. However, radiomics requires manual interventions for both image segmentation and feature extraction, indicating that its working principle cannot be separated from the essence of semi-qualitative and semi-quantitative data [ 17 , 18 ]. Moreover, the results are affected by subjective factors, resulting in poor prediction performance.…”
Section: Discussionmentioning
confidence: 99%